Hypervelocity Impacts on Honeycomb Core Sandwich Panels Filled with Shear Thickening Fluid. (April 2021) - Warren, Justin; Cole, Mike; Offenberger, Sean; Kota, Kalyan Raj; Lacy, Thomas E.; Toghiani, Hossein; Burchell, Mark; Kundu, Santanu; Pittman, Charles U.
Highlights: Hypervelocity impact testing of fluid-filled metallic honeycomb core sandwich panels Comparison of hypervelocity impacts to PEG-filled and STF-filled Panels STF-filled panels provide greater impact mitigation than PEG-filled panels at 21°C STF-filled panels subjected to hypervelocity impacts at low-temperatures (-80°C) 2D and 3D CT scans of all tested panels for damage evaluation Abstract: The use of honeycomb core sandwich panels filled with a shear thickening fluid (STF) as a component of spacecraft micrometeoroid/orbital debris (MMOD) shielding was investigated using hypervelocity impact (HVI) testing. Incorporating a STF into shielding has the potential to reduce damage to the core and the likelihood of back-side facesheet perforation in the event of a HVI. The sandwich panels tested consisted of 1.27 cm thick hexagonal aluminum honeycomb core bonded between 0.064 cm thick aluminum facesheets. The STF displayed a marked rise in viscosity with increasing shear rate above a critical shear rate. It was based on low molecular weight polyethylene glycol (PEG) and hydrophilic fumed silica. Sandwich panel target specimens filled with the STF were subjected to HVIs by 1 mm diameter stainless steel spheres at nominal temperatures of -80°C or 21°C with nominal impact velocities of 4.8 km/s or 6.8 km/s. Additional specimens filled with PEG only were also impacted for comparison. Visual inspections and X-ray computerized tomography were used to assess impact damage. All of the panels experienced perforation of the impacted facesheet, facesheet bulging, localized delamination, and the formation of a cavity in the damaged core. STF-filled panels sustained significantly less damage than PEG-filled panels. None of the STF-filled panels were completely perforated during impact. In contrast, one of the PEG-filled panels impacted at the peak velocity was perforated. The remaining PEG-filled panel sustained substantially more honeycomb core damage and facesheet-core delamination compared to an analogous STF-filled panel. Sandwich panels filled with the STF provide superior HVI mitigation in comparison to panels filled with a Newtonian fluid ( i.e., PEG). These experiments show that incorporation of STFs into MMOD shielding components has the potential to dramatically improve the HVI penetration resistance over a broad range of impact velocities and temperatures.